Comparative analyses of wetland plant biomass accumulation and litter decomposition subject to in situ warming and nitrogen addition - Yu, Xiaofei; Guo, Jiawei; Lu, Xianguo; Wang, Guoping; Jiang, Ming; Zou, Yuanchun (The Science of the total environment, 2019)
The effects of climate warming on boreal wetland plant structure and carbon (C) sequestration on local scale may be overestimated. An in situ passive warming experiment manipulated by open-top chambers and artificial nitrogen (N) addition was deployed in a lacustrine wetland of Xingkai Lake for 3 consecutive years. The annual changes and allocations of the aboveground biomass of Glyceria spiculosa, and decomposition dynamics of the total litter and cotton strips as standard references were observed. Results showed that the aboveground biomass was significantly affected by warming and increased from 99.43 ± 10.59 g m−2 (ambient) to 112.02 ± 8.08 g m−2 (ca. +1 °C) and 117.21 ± 9.92 g m−2 (ca. +2 °C). N addition had a more positive effect on the annual aboveground biomass accumulations than warming, for the relative importance weights of N addition were 2.60 and 1.49 times greater than warming in 2011 and 2013 respectively. Their main effects on the allocations had significant interannual variations, and their interaction effects were dependent on organ and year. The decomposition constant (k-value) of the litter and cotton strips were 0.747 yr−1 and 2.057 yr−1, respectively. Compared to warming and N addition, the internal quality characterized by Lignocellulose index and soil organisms reflected by litterbag size played overwhelming role in decomposition dynamics, with 2 orders greater of relative importance weights in 2011 and 2012. Our results highlight the importance of interannual variation for differentiating the contributions of external and internal factors to boreal wetland plant biomass accumulation and decomposition. Given the asymmetric responses of accumulation and decomposition, the C storage in the litter would increase in long term. [Display omitted] •In situ warming and N addition were set to test biomass and litter dynamics.•N addition had a more positive effect on biomass accumulations than warming.•N addition and warming were too small to affect litter decomposition dynamics.•Their effects were time-dependent with interannual variations.•C storage in litter compartment would increase for asymmetric responses.